Serum exosomal microRNA pathway activation in placenta accreta spectrum: pathophysiology and detectionAJOG Global Reports at a Glance - Jessian L. Munoz, MD, PhD, MPH; Brett D. Einerson, MD; Robert M. Silver, MD; Sureshkumar Mulampurath, PhD; Lauren S. Sherman, PhD; Pranela Rameshwar, PhD; Egle Bytautiene Prewit, PhD; Patrick S. Ramsey, MD, MSPH (AJOG Global Reports, 2024)
BACKGROUND: Placenta accreta spectrum disorders are a complex range of placental pathologies that are associated with significant maternal morbidity and mortality. A diagnosis of placenta accreta spectrum relies on ultrasonographic findings with modest positive predictive value. Exosomal microRNAs are small RNA molecules that reflect the cellular processes of the origin tissues. OBJECTIVE: We aimed to explore exosomal microRNA expression to understand placenta accreta spectrum pathology and clinical use for placenta accreta spectrum detection. STUDY DESIGN: This study was a biomarker analysis of prospectively collected samples at 2 academic institutions from 2011 to 2022. Plasma specimens were collected from patients with suspected placenta accreta spectrum, placenta previa, or repeat cesarean deliveries. Exosomes were quantified and characterized by nanoparticle tracking analysis and western blotting. MicroRNA were assessed by polymerase chain reaction array and targeted single quantification. MicroRNA pathway analysis was performed using the Ingenuity Pathway Analyses software. Placental biopsies were taken from all groups and analyzed by polymerase chain reaction and whole cell enzyme-linked immunosorbent assay. Receiver operating characteristic curve univariate analysis was performed for the use of microRNA in the prediction of placenta accreta spectrum. Clinically relevant outcomes were collected from abstracted medical records. RESULTS: Plasma specimens were analyzed from a total of 120 subjects (60 placenta accreta spectrum, 30 placenta previa, and 30 control). Isolated plasma exosomes had a mean size of 71.5 nm and were 10 times greater in placenta accreta spectrum specimens (20 vs 2 particles/frame). Protein expression of exosomes was positive for intracellular adhesion molecule 1, flotilin, annexin, and CD9. MicroRNA analysis showed increased detection of 3 microRNAs (mir-92, -103, and -192) in patients with placenta accreta spectrum. Pathway interaction assessment revealed differential regulation of p53 signaling in placenta accreta spectrum and of erythroblastic oncogene B2 or human epidermal growth factor 2 in control specimens. These findings were subsequently confirmed in placental protein analysis. Placental microRNA paralleled plasma exosomal microRNA expression. Biomarker assessment of placenta accreta spectrum signature microRNA had an area under the receiver operating characteristic curve of 0.81 (P<.001; 95% confidence interval, 0.73–0.89) with a sensitivity and specificity of 89.2% and 80%, respectively. CONCLUSION: In this large cohort, plasma exosomal microRNA assessment revealed differentially expressed pathways in placenta accreta spectrum, and these microRNAs are potential biomarkers for the detection of placenta accreta spectrum.